The Therapeutic Potential of Low-Intensity Pulsed Ultrasound in Enhancing Gallbladder Function and Reducing Inflammation in Cholesterol Gallstone Disease - Fang Chen; Run Guo; Tian Chen; Liping Liu; Fan Ding; Gang Zhao; Bo Zhang (Bioengineering)
Background: Cholesterol gallstone disease (CGS) is often accompanied by gallbladder contraction dysfunction and chronic inflammation, but effective therapeutic options remain limited. This study investigates whether a low-intensity pulsed ultrasound (LIPUS) treatment can improve gallbladder motility and alleviate chronic inflammation while exploring the underlying mechanisms. Methods: Gallbladder motility was assessed through in vitro and in vivo contraction tests, while bile condition was evaluated by observing bile crystal clearance. Tissue analysis and Western blotting were performed to examine the expression of the cholecystokinin A receptor (CCKAR) and α-smooth muscle actin (α-SMA) as markers of gallbladder smooth muscle health and the inflammatory microenvironment. Blood cholesterol levels were measured via biochemical assays. Results: LIPUS treatment obviously enhanced gallbladder contractility in response to CCK-8 stimulation and accelerated bile crystal clearance. It also reduced inflammatory cell infiltration and tissue edema, and promoted new capillary formation in the gallbladder, mitigating the progression of CGS. Furthermore, LIPUS restored CCKAR expression and improved the thickness of the gallbladder smooth muscle layer, providing a structural basis for increased smooth muscle contractility. Conclusion: LIPUS improves gallbladder motility and reduces chronic inflammation in CGS by enhancing CCKAR expression and smooth muscle integrity. These findings highlight the potential of LIPUS as a non-invasive therapeutic approach for managing CGS.